2019
DOI: 10.1002/1873-3468.13384
|View full text |Cite
|
Sign up to set email alerts
|

Orphan nuclear receptor NR4A1 suppresses hyperhomocysteinemia‐induced hepatic steatosis in vitro and in vivo

Abstract: Homocysteine (Hcy) is associated with nonalcoholic fatty liver disease (NAFLD). orphan nuclear receptor subfamily 4 group A member 1 (NR4A1) is involved in hepatic lipid metabolism. However, the potential role of NR4A1 in Hcy‐associated NAFLD remains elusive. We aimed to elucidate the regulation of NR4A1 and its significance in Hcy‐induced NAFLD. Hcy induced steatosis and elevated the expression of CD36 and FATP2 in HepG2 cells. Furthermore, Hcy enhanced p300 and decreased HDAC7 recruitment to the NR4A1 promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Besides, Snail1 could mediate deacetylation of H3K27 and suppress fatty acid synthase (FASN) expression, through which prevents NAFLD in obesity [14]. Another report mentioned that homocysteine (Hcy) could increase H3K27ac and modulate steatosis [15]. However, the roles and mechanisms of H3K27ac in NAFLD were not well explained, due to the tremendous genes it might affect.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Snail1 could mediate deacetylation of H3K27 and suppress fatty acid synthase (FASN) expression, through which prevents NAFLD in obesity [14]. Another report mentioned that homocysteine (Hcy) could increase H3K27ac and modulate steatosis [15]. However, the roles and mechanisms of H3K27ac in NAFLD were not well explained, due to the tremendous genes it might affect.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our research was a secondary analysis of existing data, which lacked direct experimental validation. On the other hand, Liang et al [ 44 ] reported that depletion of NR4A1 exacerbated Homocysteine-induced NAFLD, suggesting a protective role of NR4A1 against NAFLD. The inconsistencies between these studies and ours may also stem from the variations in the NAFLD models employed and the methods for inducing NR4A1 loss or gain-of-function.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Given the liver’s crucial role in the development, progression, and treatment prognosis of NAFLD, the regulation of cholesterol homeostasis has become a topic of interest in recent years. Studies have demonstrated the important role of NRs in regulating and stabilizing hepatic lipid metabolism 31 37 (Fig. 1 ).…”
Section: Nafld Pathogenesismentioning
confidence: 99%
“…As the ligands for many NRs are fatty acids, steroids, and oxysterols, their role in liver lipid metabolism has received extensive attention. 36 , 37 , 52 54 Table 1 lists the NRs involved in cholesterol metabolism and NAFLD. In the following sections, we summarize the roles of several NRs in maintaining hepatic cholesterol homeostasis and in the development and progression of NAFLD.…”
Section: Nuclear Receptorsmentioning
confidence: 99%